2021
DOI: 10.1002/mp.15333
|View full text |Cite
|
Sign up to set email alerts
|

Clinical suitability of deep learning based synthetic CTs for adaptive proton therapy of lung cancer

Abstract: Purpose Adaptive proton therapy (APT) of lung cancer patients requires frequent volumetric imaging of diagnostic quality. Cone‐beam CT (CBCT) can provide these daily images, but x‐ray scattering limits CBCT‐image quality and hampers dose calculation accuracy. The purpose of this study was to generate CBCT‐based synthetic CTs using a deep convolutional neural network (DCNN) and investigate image quality and clinical suitability for proton dose calculations in lung cancer patients. Methods A dataset of 33 thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 44 publications
2
29
1
Order By: Relevance
“…Proton 45 and photon 52 abdominal plans were validated once, and a single‐photon lung plan was validated for the stricter 2%/2‐mm criteria 49 . However, no study has investigated sCT accuracy for proton breast plans, whereas the single study that analyzed proton lung plans failed to demonstrate sufficient dosimetric accuracy 59 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Proton 45 and photon 52 abdominal plans were validated once, and a single‐photon lung plan was validated for the stricter 2%/2‐mm criteria 49 . However, no study has investigated sCT accuracy for proton breast plans, whereas the single study that analyzed proton lung plans failed to demonstrate sufficient dosimetric accuracy 59 …”
Section: Discussionmentioning
confidence: 99%
“…The lung site was well validated for photon plans 40,42,49 for a 3%/3-mm criteria; however, two investigations noted failing 2%/2-mm rates. A single study by Thummerer et al 59 investigated the lung site for proton ART and reported passing rates only for 3%/3-mm criteria.…”
Section: Sct Dosimetrymentioning
confidence: 99%
See 2 more Smart Citations
“…Van der Heyden et al presented a single detector, multi-energy proton radiography system which relied on artificial intelligence to filter out proton scatter (198). In addition, multiple studies have been reported which utilize deep learning as a tool to facilitate accurate proton dose calculation from daily CBCT images (121,(199)(200)(201). Elmahdy et al also reported on a convolutional neural network (CNN)-based model for robust, automatic contour propagation in prostate cancer for online adaptive proton therapy (202).…”
Section: Artificial Intelligencementioning
confidence: 99%